2023
DOI: 10.1002/gj.4666
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of machine learning‐based methods in landslide susceptibility mapping

Abstract: Landslide susceptibility mapping (LSM) has been widely used as an important reference for development and construction planning to mitigate the potential social‐eco impact caused by landslides. Originally, most of those maps were generated by the judgements of experts, which is time‐consuming and laborious, and whose accuracy is difficult to be quantified because of the subjective effects. With the development of machine learning algorithms and the methods of data collection, big data and artificial intelligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(30 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…Although the Transformer-based SegFormer network shows superior performance over the CNNbased network in several datasets [20,21,22], the CNN-based network still shows excellent performance for the crack image data in this study. In addition, the SS network can achieve more accurate segmentation in the dataset reconstructed based on RCAN, and the overall structure and detail aspects of the detected cracks best match the labeled data.…”
Section: Performance Comparison Of Classifier Modelsmentioning
confidence: 66%
See 1 more Smart Citation
“…Although the Transformer-based SegFormer network shows superior performance over the CNNbased network in several datasets [20,21,22], the CNN-based network still shows excellent performance for the crack image data in this study. In addition, the SS network can achieve more accurate segmentation in the dataset reconstructed based on RCAN, and the overall structure and detail aspects of the detected cracks best match the labeled data.…”
Section: Performance Comparison Of Classifier Modelsmentioning
confidence: 66%
“…With the rapid development of CV technology, some novel algorithms such as FCN, Deeplab V3+ and FraSegNet are gradually being applied to the recognition and parsing of various research objects and have shown better performance in feature extraction [14,15,16,17,18,19]. The feature extracted by the latest Transformer-based algorithms such as SETR, TransUNet and SegFormer have richer global contextual information, which overcomes the drawback that convolutional neural network-based (CNN) algorithms cannot directly extract long-range information and eventually show excellent performance in semantic segmentation tasks [20,21,22]. However, in the case of regional rock crack images, the selection of hyperparameters in the feature extraction process is highly dependent on the image resolution and specific scene features.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of coastal banks is affected by the changing water levels, rainfall, and earthquakes (Sassa and Takagawa, 2019;Liu et al, 2023). The reliability evaluation method of reservoir banks under various disaster-causing factors in this paper can be applied to predict the long-term safety of the coastal banks (Cavanaugh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Du et al and Jia et al further conducted experimental research on dumping perilous rock and found that the natural vibration frequency is closely related to the stability [30][31][32][33]. However, the above research has just started and is in the experimental stage, and the theory has not yet been perfected [34,35]. And the above test found that the dynamic characteristic parameters of the perilous rock are closely related to the stability [36].…”
Section: Introductionmentioning
confidence: 99%